2020
DOI: 10.5194/bg-17-6219-2020
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile organic compound ambient mixing ratios and emission rates in the Alaskan Arctic tundra

Abstract: Abstract. Rapid Arctic warming, a lengthening growing season, and the increasing abundance of biogenic volatile-organic-compound-emitting shrubs are all anticipated to increase atmospheric biogenic volatile organic compounds (BVOCs) in the Arctic atmosphere, with implications for atmospheric oxidation processes and climate feedbacks. Quantifying these changes requires an accurate understanding of the underlying processes driving BVOC emissions in the Arctic. While boreal ecosystems have been widely studied, li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 94 publications
(236 reference statements)
6
18
1
Order By: Relevance
“…Our study showed that experimental warming by ~3°C doubled emissions of total VOCs, monoterpenes, and GLVs. This agrees with several recent studies showing the high sensitivity of plant VOC emissions to temperature rise in the Arctic (Angot et al, 2020;Kramshøj et al, 2016a;Rinnan et al, 2020). While a recent study by Young et al, (2019) found little increase in summer temperatures over recent decades in Northern Fennoscandia, due to increased cloud cover, the high sensitivity of plant VOC emissions to the local temperature increases in the Arctic (Ghirardo et al, 2020;Seco et al, 2020) suggests that even small temperature increases may have strong impacts on plant VOC emissions, with large implications for the atmospheric chemistry processes.…”
Section: Main Effects Of Warming and Shadingsupporting
confidence: 93%
“…Our study showed that experimental warming by ~3°C doubled emissions of total VOCs, monoterpenes, and GLVs. This agrees with several recent studies showing the high sensitivity of plant VOC emissions to temperature rise in the Arctic (Angot et al, 2020;Kramshøj et al, 2016a;Rinnan et al, 2020). While a recent study by Young et al, (2019) found little increase in summer temperatures over recent decades in Northern Fennoscandia, due to increased cloud cover, the high sensitivity of plant VOC emissions to the local temperature increases in the Arctic (Ghirardo et al, 2020;Seco et al, 2020) suggests that even small temperature increases may have strong impacts on plant VOC emissions, with large implications for the atmospheric chemistry processes.…”
Section: Main Effects Of Warming and Shadingsupporting
confidence: 93%
“…This demonstrates that the performance of 𝜸 T varies across ecosystems, and that any updates to the parameterization of 𝜸 T should be applied on an ecosystem-specific scale. This has been done previously for Australian eucalypt species (Emmerson et al, 2020), and other studies have demonstrated that this may also be necessary for Arctic vegetation (Angot et al, 2020;Kramshøj et al, 2016;Seco et al, 2020Seco et al, , 2022. Accurately modeling the sensitivity of isoprene emissions to temperature will depend on the development of an ecosystem-specific parameterization for 𝜸 T , which could be derived using our methodology wherever suitable observations are available.…”
Section: Variability Of 𝜸 T Between Ecosystemsmentioning
confidence: 90%
“…Model performance is generally good when accurate driving variables are used (Situ et al, 2014; see also Filella et al, 2018;Sarkar et al, 2020), but significant sources of uncertainty remain. These include the empirical parameterization of the standard emission rates and the dimensionless scaling functions, particularly the temperature and drought stress responses (Angot et al, 2020;Guenther et al, 2006;X. Jiang et al, 2018;Kramshøj et al, 2016;Potosnak et al, 2014;Seco et al, 2015Seco et al, , 2020Seco et al, , 2022.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, tundra ecosystems are highly heterogeneous and tundra plant responses to warming vary greatly (Bjorkman et al, 2018;Collins et al, 2021). Indeed, previous studies have indicated the unique specificity of tundra VOC emissions as a function of location and vegetation type (Angot et al, 2020;Ghimire et al, 2021;Kramshøj et al, 2016). Thus, field studies in other high-latitude regions are needed to provide a more comprehensive understanding of the sources and drivers of VOC emissions from high-latitude ecosystems.…”
Section: Introductionmentioning
confidence: 99%